ANTIOXIDANT CAPACITY OF PEPTIDES DERIVED FROM THE ENZYMATIC HYDROLYSIS OF RAINBOW TROUT (Oncorhynchus mykiss) SKIN: EFFECT OF PASTEURIZATION AND ULTRASONICATION PRE-TREATMENT - Escamilla Rosales, María Fernanda; Jara Gutiérrez, Carlos Esteban; Bautista Ávila, Mirandeli; Castañeda Ovando, Araceli; Álvarez Álvarez, Claudio; Santana Sepúlveda, Paula Andrea; González Olivares, Luis Guillermo (Journal of the Chilean Chemical Society, 2025)
Rainbow trout skin and viscera are considered non-commercial by-products with high protein content. This research aimed to determine the incidence of pasteurization and ultrasonication during the obtaining of antioxidant peptides by the hydrolysis of trout skin proteins with Alcalase and Flavourzyme. Solutions of freeze-dried skin were prepared (20 % w/v), and two pretreatments were performed: pasteurization (90 ºC for 10 min) and a combination of pasteurization and ultrasonication (40 kHz x 15 min). Hydrolysis was for 8 hours with Alcalase (pH 9, 55°C) and Flavourzyme (pH: 7, 50°C) sampling every 2 hours. The degree of hydrolysis was determined by TNBS and SDS-PAGE. Antioxidant activity was determined by DPPH and FRAP. The ultrasonication does not affect the release of peptides with antioxidant capacity. In addition, greater antioxidant capacity was determined in hydrolysates with Flavourzyme. Results would allow establishing the conditions for the optimized obtaining of this type of peptide fractions.